2003
DOI: 10.1046/j.1432-1033.2003.03907.x
|View full text |Cite
|
Sign up to set email alerts
|

Glutamate signaling in peripheral tissues

Abstract: The hypothesis that L-glutamate (Glu) is an excitatory amino acid neurotransmitter in the mammalian central nervous system is now gaining more support after the successful cloning of a number of genes coding for the signaling machinery required for this neurocrine at synapses in the brain. These include Glu receptors (signal detection), Glu transporters (signal termination) and vesicular Glu transporters (signal output through exocytotic release). Relatively little attention has been paid to the functional exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
138
0
5

Year Published

2005
2005
2014
2014

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 188 publications
(147 citation statements)
references
References 188 publications
2
138
0
5
Order By: Relevance
“…Recently, Chevassus et al (2002) gave 10 g MSG or placebo in capsules orally to fasted human subjects at the time they received a 75 g glucose load, and followed the plasma insulin changes over time. There was a significant positive correlation between plasma insulin area-under-thecurve and peak plasma GLU concentrations, suggesting to the authors that GLU enhanced glucose-induced insulin secretion, consistent with the existence of stimulatory GLU receptors on pancreatic beta cells (Hinoi et al, 2004). In this study, peak plasma GLU concentrations were about doubled over baseline and placebo values.…”
Section: Central Nervous Systemsupporting
confidence: 86%
“…Recently, Chevassus et al (2002) gave 10 g MSG or placebo in capsules orally to fasted human subjects at the time they received a 75 g glucose load, and followed the plasma insulin changes over time. There was a significant positive correlation between plasma insulin area-under-thecurve and peak plasma GLU concentrations, suggesting to the authors that GLU enhanced glucose-induced insulin secretion, consistent with the existence of stimulatory GLU receptors on pancreatic beta cells (Hinoi et al, 2004). In this study, peak plasma GLU concentrations were about doubled over baseline and placebo values.…”
Section: Central Nervous Systemsupporting
confidence: 86%
“…Besides the function as a neurotransmitter, glutamate is a general metabolic substrate. The presence of VGluT in non-neuronal tissues such as calcified tissues has been reported (see review Hinoi et al, 2004). Therefore, glutamate has metabotropic effects in the Ruffini endings.…”
Section: Vglut In Ruffini Endingsmentioning
confidence: 99%
“…L-glutamate is the most widely investigated amino acid as a signaling molecule [6], having receptors on human lymphocytes [7]. The current in vivo study showed that glutamate concentration increased significantly 90 minutes after breakfast, it reached the values of 2.28 + 1.76 x10 -4 M but it returned near the fasting value at 150 minutes.…”
Section: Discussionmentioning
confidence: 52%
“…In addition to its important role as a neurotransmitter, glutamate signaling has been described in peripherial tissues, e.g. in bone, pancreas, skin [6]. Furthermore, ionotropic glutamate receptors have been characterized in human lymphocytes [7].…”
Section: Introductionmentioning
confidence: 99%